Metabolic profiles and potential antioxidant mechanisms of hawk tea - Sixia Jiang; Hong Zhang; Ya Song; Mingji Xiao; Hao Hu; Shirui Yu; Feng Xie (Scientific Reports)
Abstract Hawk tea has received increasing attention for its unique flavor and potential health benefits, with antioxidant function being one of its significant bioactivities. However, the metabolic profiles, potential antioxidant components, and action mechanisms of different types of hawk tea are still unclear. In this study, the chemical components of five hawk teas were determined using untargeted metabolomics. Then, the potential antioxidant metabolites and their possible action mechanisms were revealed by integrating network pharmacology and molecular docking. The results showed that the metabolic profiles of various hawk teas differed significantly, but the content of flavonoids was the highest in each group. Network pharmacology analyses suggested that 11 potential antioxidant metabolites—four of which were the same metabolites with high levels in the five types, and seven were differential metabolites—could be involved in several metabolic pathways in vivo. These pathways included the MAPK and PI3K/AKT signaling pathways, which may be closely related to antioxidant activity. Finally, molecular docking revealed potential antioxidant metabolites bound to 25 core antioxidant targets through hydrogen bonding and hydrophobic interactions. Among them, artemisinin, astragalin, isoquercetrin, isoquercitrin, kaempferol-3-glucuronide, and UDP-L-rhamnose exhibited low binding energies to core antioxidant targets such as AKT1, RELA, and MTOR, forming stable conformation. These insights lay the basis for further elucidating the antioxidant mechanism of hawk tea.